A deep dive into testing and management of COVID-19 for Australian high performance and professional sport - Mooney, M.; Panagodage Perera, N. K.; Broderick, C.; Saw, R.; Wallett, A.; Drew, M.; Waddington, G.; Hughes, D. (Journal of Science and Medicine in Sport, 2020)
The purpose of testing for any communicable disease is to support clinicians in the diagnosis and management of individual patients and to describe transmission dynamics. The novel coronavirus is formally named SARS-CoV-2 and the clinical disease state resulting from an infection is known as COVID-19. Control of the COVID-19 pandemic requires clinicians, epidemiologists, and public health officials to utilise the most comprehensive, accurate and timely information available to manage the rapidly evolving COVID-19 environment. High performance sport is a unique context that may look towards comprehensive testing as a means of risk mitigation. Characteristics of the common testing options are discussed including the circumstances where additional testing may be of benefit and considerations for the associated risks. Finally, a review of the available technology that could be considered for use by medical staff at the point of care (PoC) in a high-performance sporting context is included.